Adolescent Health - World Bank (Washington, DC, 2012)
More than a quarter of the world's population is between the ages of 10 and 24. Most (86 percent) of the world's 1.7 billion young people live in developing countries, where they are often 30 percent or more of the population. At first glance, youth appears to be a relatively healthy although not hazard-free period of life. Young people account for 15 percent of the disease and injury burden worldwide and over one million die each year, mainly from preventable causes. Nonetheless, roughly 70 percent of premature deaths among adults can be linked to behavior initiated during adolescence, such as tobacco use, poor eating habits, and risky sex. Investing in health and development of young people is not only the right thing to do, it's the smart thing for countries that want their economies to grow faster: 1) reducing HIV infection in young people will reduce the devastating economic impact of HIV/AIDS; 2) when young people postpone marriage and childbearing, family size falls and population growth slows. Combined with investments in health and education, these changes contribute to higher economic growth and incomes; and 3) investments to head off negative behaviors such as tobacco use and drug abuse will pay off later for individuals and for society.